Impact of storage temperature and duration on ethanol content in juice and soft drinks - Sharinazainor Sharina, Mohamed Shariff; Nur Hajarrul Atika, Adnan; Nazikussabah, Zaharudin (Penerbit Universiti Malaysia Pahang, 2023)
The ethanol content in beverages can be impacted by storage conditions, presenting potential implications for product quality and consumer safety. The study examined the impact of storage temperature and duration on ethanol levels in various beverages, including sugarcane juice, grape juice, and soft drinks. The findings suggest that storage conditions significantly influence ethanol production, particularly in sugarcane juice. Storing sugarcane juice at 28°C for 14 days resulted in a substantial increase in ethanol content, from 2.11% to 7.32% alcohol by volume (ABV). In contrast, grape juice exhibited moderate ethanol increases, and soft drinks showed minimal changes, with ethanol peaking at 0.95% ABV. These results highlight the accelerated fermentation process in sugarcane juice under higher temperatures and underline the importance of maintaining strict storage conditions to preserve beverage quality. Comparative analysis indicates that sugarcane juice is highly susceptible to ethanol generation when stored at room temperature, emphasizing the necessity of refrigeration to maintain its safety and flavor profile.